Theory and simulation of liquids and liquid mixtures - Pallewela, Gayani Nadeera (Kansas State University, 2016)
Kirkwood Buff (KB) theory is one of the most important theories of solutions. The theory can relate integrals over radial (pair) distribution functions (rdfs) in the grand canonical ensemble to common thermodynamic properties. An inversion of the KB theory has been proposed by Ben-Naim and this has led to the wide spread popularity of KB theory. The idea of the KB inversion procedure is to calculate KB integrals from available thermodynamic properties. The KB theory can be used to validate the force field (ff) parameters used in molecular dynamics simulations. We have tested a series of small molecule ff parameters using KB theory that consists of both atom centered partial atomic charges and extra charge sites. The results indicate that using extra charge sites, derived from QM calculations, does not necessarily provide a more accurate representation of condensed phase properties. A further study aimed at an ongoing project of deriving new biomolecular ff parameters based on KB theory, has developed ff parameters for esters in order to represent the ester conjugation of the phospholipid molecule. The models were further tested against experimental properties. Preferential solvation (PS) is an important concept of solution mixtures that can be described using KB theory. The difference between local composition and bulk composition in solution mixtures leads to the concept of PS. A generalized explanation based on local mole fractions was derived by Ben-Naim using KB theory. However, the original expressions have been modified over years. Here, we propose a new approach based on local volume fractions to explore PS in binary and ternary solution mixtures. Experimental and simulation data were used to examine different approaches to PS. A relationship between the rdf and the triplet distribution function can be obtained using the Kirkwood Superposition Approximation (KSA). A combination of Fluctuation Solution Theory and experimental rdfs are used to examine the KSA at a series of state points for pure water. The accuracy of several other approximate relationships between the pair and triplet correlation functions was also investigated and are in good agreement for regions of the phase diagram where the compressibility is small.
Keywords: Kirkwood Buff Theory; Molecular Simulation; Preferential Solvation; Liquids and Liquid Mixtures; Theory; Fluctuation Solution Theory